Impact of a Physical Exercise and Health Education Program on Metabolic Syndrome and Quality of Life in Postmenopausal Breast Cancer Women Undergoing Adjuvant Treatment with Aromatase Inhibitors - Pedro Cespedes; Francisco M. Martínez-Arnau; María Dolores Torregrosa; Omar Cauli; Cristina Buigues (Medicina)
Background and Objectives: Adjuvant treatment with aromatase inhibitors (AIs) in breast cancer (BC) survivors can cause adverse effects such as metabolic syndrome (MS) (insulin resistance, central obesity, atherogenic dyslipidemia, and hypertension) associated with morbidity and premature mortality. We evaluate the effect of a multimodal program based on physical exercise and health education on MS and health-related quality of life (QoL) in postmenopausal women with BC under AIs. Methods: A total of 56 postmenopausal women, diagnosed with BC, aged 60 years or older (mean age 67.2 years) and on hormonal treatment with AIs, were included in the multimodal physical exercise and health education program, and evaluated before and after their participation. The assessment of the five criteria of the MS included the following: waist circumference, high blood pressure, fasting glucose, triglycerides, and high-density lipoprotein cholesterol. Two main instruments were used to evaluate the impact of the intervention on QoL: the EORTC QLQ C30 (questionnaire for cancers in general) and the EORTC QLQ BR23 (specifically for breast cancer patients). The EuroQol 5D (EQ-5D) was also used to compare these results. Results: The percentage of women meeting the MS criteria was 37.7% at baseline and fell to 15.1% at 3 months after the intervention (p = 0.02). The intervention significantly reduced hypertension (p < 0.001), central obesity (p < 0.001), and the concentration of triglycerides (p = 0.016). No significant changes were observed in fasting glucose and HDL concentration. A statistically significant improvement was found in QoL (on both the QLQ30 and BR23 scales). A multivariate regression model analysis identified marital status (being married) (95% CI: 1.728–131.615, p = 0.014), and percentage of attendance at health education sessions (95% CI: 1.010–1.211, p = 0.029) as positive predictive variables of improvement in MS. Conclusions: The implementation of multimodal, community-based programs of physical exercise and health education improve the prevalence of MS and specific criteria of MS and QoL in postmenopausal women with breast cancer receiving AI treatment.